تشكيلات الجندرمة في ولاية اليمن خلال حكم الوالي إسماعيل حقي باشا ( 1878 – 1891 م ) - شلتاغ, بان راوي (Journal of College of Education, 2018)
The study examines gendarmes in the state of Yemen. The Gendarmerie forces of Hamidiya were formed in 1878 in the state of Yemen during the reign of the governor, Ismail Hakki Pasha, who ruled for the first time (1878-1882). They were Yemenis, especially tribesmen living in the mountainous regions. But the Ottoman Sultan ordered the cancellation of these regiments for fear that it would be the beginning of the independence of the state of Yemen from the Ottoman Empire. In the second term of the mandate of Ismail Hakki Pasha (1890 - 1891), these gendarmes became They call the exact and they are from the oasis Yin.The organization of the gendarmerie forces at the beginning of the formation of the first regiment of infantry consists of four brigades and the third regiment and consists of a single division divided into four groups distributed throughout the state, and in 1890 became Gendarme Hamidiya called the police, and became more regular and regular, became a board of directors, Of four regiments, each with infantry and infantry.Their duties were to maintain security in the country, to carry out government services throughout the state, to quell sedition and rebel movements, and have succeeded in being Yemenis and able to influence the people to achieve security